The role of the IMF in the European debt crisis - Franz Seitz; Thomas Jost (Hochschule für angewandte Wissenschaften Amberg-Weiden (HAW), 2012)
This paper gives an overview of the role of the IMF in the European debt crisis. It describes the rescue packages and the involvement of the IMF. The main part discusses the pros and cons of the participation of the IMF in elaborating and monitoring the economic adjustment programs for the countries in crisis. A last section concludes and tries to answer the question whether the Troika model might be suited to solve future international crises.
Keywords: F02; F53; F59; 330; IMF; Europe; debt; euro